Gecko CD59 Is Implicated in Proximodistal Identity during Tail Regeneration - Wang, Yongjun; Wang, Ruili; Jiang, Shengjuan; Zhou, Weijuan; Liu, Yan; Wang, Yingjie; Gu, Qing; Gu, Yun; Dong, Yingying; Liu, Mei; Gu, Xingxing; Ding, Fei; et al. (PLOS ONE, 2011)
Several adult reptiles, such as Gekko japonicus, have the ability to precisely re-create a missing tail after amputation. To ascertain the associated acquisition of positional information from blastemal cells and the underlying molecular mechanism of tail regeneration, a candidate molecule CD59 was isolated from gecko. CD59 transcripts displayed a graded expression in the adult gecko spinal cord with the highest level in the anterior segment, with a stable expression along the normal tail. After tail amputation, CD59 transcripts in the spinal cord proximal to the injury sites increased markedly at 1 day and 2 weeks; whereas in the regenerating blastema, strong CD59 positive signals were detected in the blastemal cells anterior to the blastema, with a gradual decrease along the proximodistal (PD) axis. When treated with RA following amputation, CD59 transcripts in the blastema were up-regulated. PD confrontation assays revealed that the proximal blastema engulfed the distal one after in vitro culture, and rabbit-anti human CD59 antibody was able to block this PD engulfment. Overexpression of the CD59 during tail regeneration causes distal blastemal cells to translocate to a more proximal location. Our results suggest that position identity is not restricted to amphibian limb regeneration, but has already been established in tail blastema of reptiles. The CD59, a cell surface molecule, acted as a determinant of proximal–distal cell identity.